GENETIKA FANINI O'QITISHDA QO'LLANILADIGAN ZAMONAVIY YONDASHUVLAR VA INNOVATSION TEXNOLOGIYALAR - Abdullayeva Gulzebo (TADQIQOTLAR, 2026)
Abstract: This article examines modern approaches and innovative technologies used in teaching genetics and their impact on improving educational effectiveness. The study highlights learner-centered teaching methods, digital technologies, interactive learning  tools,  virtual  laboratories,  and  multimedia  resources  that  contribute  to enhancing students’ understanding of genetic concepts. Special attention is given to the integration of information and communication technologies, problem-based learning, and  practical  applications  in  genetics  education.  The  findings  suggest  that  the implementation  of  innovative  educational  strategies  increases  student  engagement, develops analytical thinking skills, and improves the quality of genetics education. The article emphasizes the importance of adapting teaching methods to modern educational requirements and technological advancements.